A REVIEW OF CHILDREN'S ILLEGAL RACING BASED ON LAW NO. 22 OF 2009 CONCERNING ROAD TRAFFIC AND TRANSPORTATION - Pradana, Haris Kondang; Chasanah, Nur; Savage, Eileen (SYNTIFIC, 2023)
Background. The occurrence of illegal racing crime is caused by poor self-control of children and also weakening social control due to lack of family supervision, environment, school, and law enforcement to carry out their control functions. The study aimed to identify the chronology and illegal motorcycle street racing area that became a favorite place where illegal racers held in Ploso Kertosono Nganjuk and the surrounding area. Research Method. This research is considered as a field research or case study. It is used descriptive analysis method and the type of research is qualitative research. The data collection procedures of this study were observation, interviews, and documentation. The primary sources included interviewing illegal riders, the society around the illegal street racing area, and police officers from the county police of Nganjuk. The secondary data were collected from books, journals, and documents. The research analyzed from Ius Constitutum included No. 22 of 2009 about Indonesian traffic law. Findings. This research results more on the chronology and describes the flow of illegal races that are so popular with children in the Ploso Kertosono Nganjuk road area and its surroundings in Nganjuk Regency and is continued with an analysis in terms of Positive Law in the form of Law No. 22 of 2009 concerning Road Traffic and Transportation. The final result is the absolute truth of Positive Law in analyzing illegal racing under applicable laws and regulations. Conclusion. The concept of Ius Constitutum analyzes illegal motorcycle street racing according to the applicable laws and regulations.